The great controversy in a nutshell - Hoppe, Maurice (Middleton, ID : CHJ Publishing : Distributed by Revelation Ministry, 1998)
A very brief discussion of the conflict between Christ and Satan, especially the closing events and the involvement of the people of the world.
Keywords: Seventh-Day Adventists -- Doctrines; Church history; Eschatology